(untitled) (Revista Educação, Artes e Inclusão, 2022)
The integrated concepts between dance, education and leisure were analyzed based on the project The Integral Education on the city stages, in Belo Horizonte - MG. The project takes in the municipal public education network, primarily serving less afluente communities. The process involves the creation of a dance performance in the context of integral education, the occupation of theaters in the city and na educational and a esthetic experience on stage and in the audience for the participants. Analyzes and reports of the interviewed monitors highlight the need for educational actions for the entire network of stake holders and the power of dance in this experience and in the awareness of the right to leisure.